Hound dog the Leiber and Stoller autobiography - Leiber, Jerry 1933-2011; Stoller, Mike 1933- (Simon & Schuster, 2009)
In 1950 a couple of rhythm and blues-loving teenagers named Jerry Leiber and Mike Stoller met, discovered their mutual affection for R&B, and, as Jerry and Mike put it in this autobiography, it was the beginning of an argument that has been going on for more than fifty years with no resolution in sight. They had their first success with a song called "Hard Times" that became an R&B hit in 1952. They followed it another bluesy composition, "Hound Dog," for the inimitable Big Mama Thornton. A few years later "Hound Dog" would become a #1 hit for Elvis Presley, and Jerry and Mike became the King's favorite songwriters. They went on to write for the Coasters, the Drifters and many others. Along the way they mentored an ambitious young writer-producer named Phil Spector and influenced musician Burt Bacharach. Here they describe how two young guys created the soundtrack for a generation.--From publisher description.
Includes bibliographical references and index
Keywords: Leiber, Jerry; Stoller, Mike; Stoller, Mike -- 1933-; Leiber, Jerry -- 1933-2011; Geschichte; Lyricists -- United States -- Biography; Composers -- United States -- Biography; Rock music -- United States -- History and criticism; Rockmusik; USA; Biografie